Did Partisan voters spoil the country? A randomized-thought experiment - Victoria Barham; Ghislain-Herman Demeze-Jouatsa; Roland Pongou (Bielefeld University, Center for Mathematical Economics (IMW), 2019)
We study the effect of strategic and partisan voting on electoral outcomes, and on the relative popularity of the victor. Voters are randomly assigned to be partisan or strategic. When all voters are strategic in a plurality election, any equilibrium manipulation of the outcome elects a popular leader. Voting populations with a large proportion of partisan voters are more at risk of electing an unpopular leader: in elections with three candidates, if only one-third of the population is partisan, then the winner of the election may be unpopular with two-thirds of voters. We derive exact bounds for the proportion of the population that benefits from manipulation of the election outcome by strategic voters, for arbitrary numbers of voters, candidates, partisans and strategic voters. The analysis also shows that the unpopularity of the election winner differs between partisan and strategic voters. When most voters are partisan, they may be the vast majority of those who gain from strategic voting.
urn:nbn:de:0070-pub-29382043
Keywords: P16; D72; C7; J15; H41; 330; Morality and Politics; Partisan Voting; Winner Unpopularity; Plurality; Impact Heterogeneity; Randomization